Kecemasan Pasien COVID-19: A Systematic Review - Anis Rosatil Jannah; Atika Jatimi; Maulidiyah Junnatul Azizah Heru; Zainal Munir; Handono Fatkhur Rahman (FORIKES, 2020)
Background: Post Coronavirus Desease 2019, discovered in December 2019, then On March 18, 2020, more than 180,000 cases were confirmed and at least 7,500 deaths have been reported in 159 countries. According to the World Health Organization, a gloomy pandemic has caused increased anxiety and mental health, both positive for patients and society. Objective: To detect signs of anxiety symptoms in covid-19 patients and the effects that can be caused during the treatment period and the isolation period. Methods: Introductory literature was obtained from 10 international articles with Google Scholar with the keyword Patient Anxiety -19. The next step is to choose by counting the year of publication (2019-2020). With full technology and speak English. Furthermore, articles and journals that are considered to be less relevant are excluded. Results: anxiety is often caused by situations that include the patient, respiratory distress, reduced social activity, feelings of rejection by society and social dynamics that change dramatically. Symptoms that appear in patients are anxiety that affects the patient's sleep patterns. Conclusion: Co-19 patients tend to experience psychological disorders in the form of anxiety, fear. Psychological consequences of this attack because the patient has excessive anxiety, especially physical conditions and interaction patterns that are really limited to suppress the spread of the virus. Suggestion: The two factors above still need to be reviewed to find the cause of patient anxiety in detail. Keywords: anxiety; covid-19 ABSTRAK Latar Belakang: Pasca Coronavirus Desease 2019, ditemukan pada Desember 2019, selanjutnya Pada 18 Maret 2020, lebih dari 180.000 kasus dikonfirmasi dan setidaknya 7.500 kematian telah dilaporkan di 159 Negara. Menurut World Health Organisasi, pandemi yang suram telah menyebabkan meningkatnya kecemasan dan kesehatan mental baik pasien positif covid-19 maupun masyarakat. Tujuan: Untuk mendeteksi tanda gejala kecemasan pasien covid-19 dan efek yang dapat ditimbulkan selama masa perawatan dan masa isolasi. Metode: Literatur awal didapatkan dari 10 artikel Internasional dengan Google Scholar dengan kata kunci Patient anxiety covid-19. Tahapan selanjutnya adalah melakukan penyeleksian dengan memperhatikan tahun terbitan (2019-2020). Dengan tek penuh dan berbahasa Inggris. Selanjutnya, artikel dan jurnal yang dinilai kurang relevan dikeluarkan. Hasil: kecemasan kerap disebabkan oleh situasi yang tengah meliputi pasien, gangguan saluran pernafasan, berkurangnya kegiatan sosial, perasaan terhadap penolakan oleh masyarakat dan dinamika sosial masyarakat yang berubah drastis. Gejala yang muncul pada pasien adalah kecemasan yang berimbas pada pola tidur pasien. Kesimpulan: Pasien covid-19 rentan mengalami gangguan psikologis berupa kecemasan, ketakutan. Konsekuensi psikologis ini menyerang karena pasien memiliki kecemasan berlebih terutama kondisi fisik dan pola interaksi yang serba dibatasi dalam rangka menekan persebaran virus. Saran: Dua faktor diatas masih memerlukan kajian ulang untuk menemukan sebab kecemasan pasien secara mendetail. Kata kunci: kecemasan; covid-19